A graph theory-based approach to the description of the process and the diagnostic system - Kościelny, Jan Maciej; Bartyś, Michał; Syfert, Michał; Sztyber, Anna (Zielona Góra: Uniwersytet Zielonogórski)
The paper proposes an original, comprehensive, and methodically consistent graph theory-based approach to the description of the diagnosed process and the diagnosing system. The main baseline of the presented approach is in the dichotomous approach to diagnosing. It involves a separate description of both the process and the diagnostic system. This approach reflects the practice of designing implementable diagnostic systems. Thus, it can be seen as a proposal of a new, alternative, and, at the same time, flexible design procedure with great potential for applications.
Keywords: graph of the process; graph of the diagnostic system; fault detection and isolation; qualitative models; limitations of diagnostic approaches